Biohydrometallurgy of secondary metal resources: a potential alternative approach for metal recovery. Issue 12 (31st July 2013) - Erüst, Ceren; Akcil, Ata; Gahan, Chandra Sekhar; Tuncuk, Aysenur; Deveci, Haci
Abstract: Research on biohydrometallurgy of secondary metal resources is primarily focused on the leaching of valuable metals. For secondary metal resources biological processing can be an economically more effective and environmentally friendlier alternative to traditional hydrometallurgical and pyrometallurgical processes. Therefore, biohydrometallurgy is a rapidly evolving biotechnology that has already provided revolutionary solutions to old problems associated with recovery of metals by conventional pyrometallurgy and chemical metallurgy. This review evaluates various processes of recovery of metals from waste materials and commercial applications are discussed. Case studies and future technology directions are reviewed. © 2013 Society of Chemical Industry